Fast and low-cost synthesis of MoS2 nanostructures on paper substrates for near-infrared photodetectors - Cordeiro, Neusmar Juniar Artico (2021)
Recent advances in the production and development of two-dimensional transition metal dichalcogenides (2D TMDs) allow applications of these materials, with a structure similar to that of graphene, in a series of devices as promising technologies for optoelectronic applications. In this work, molybdenum disulfide (MoS2) nanostructures were grown directly on paper substrates through a microwave-assisted hydrothermal synthesis. The synthesized samples were subjected to morphological, structural, and optical analysis, using techniques such as scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman. The variation of synthesis parameters, as temperature and synthesis time, allowed the manipulation of these nanostructures during the growth process, with alteration of the metallic (1T) and semiconductor (2H) phases. By using this synthesis method, two-dimensional MoS2 nanostructures were directly grown on paper substrates. The MoS2 nanostructures were used as the active layer, to produce low-cost near-infrared photodetectors. The set of results indicates that the interdigital MoS2 photodetector with the best characteristics (responsivity of 290 mA/W, detectivity of 1.8 × 109 Jones and external quantum efficiency of 37%) was obtained using photoactive MoS2 nanosheets synthesized at 200◦C for 120 min.